Metadata Management in Organizations : إدارة الميتاداتا في المنظمات - Mohammed Abdullah Al- Amri (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2021)
This study aims at providing an introductory overview of "metadata management in organizations". It also tries to highlight its role for those interested in data management and governance in organizations. In addition, it aims to identify the benefits, components, challenges, and managers of metadata management in organizations. The inductive approach was used by reviewing the literature on metadata management. Results showed the most important concepts of metadata management, the obvious benefits and the active role that it provides as well as the components of metadata management. Moreover, results indicated that metadata managers and their challenges as well as some techniques to overcome them. The study recommended that organizations should pay attention to managing their data by managing metadata, making use of organizations that are pioneering in this field and seeking assistance from data experts and scientists. Contracting with companies specialized in metadata management. It also recommended qualifying and training the relevant personnel in the organization, and striving to keep pace with recent developments in data management and governance.